Microvascular remodeling and altered angiogenic signaling in human kidneys distal to occlusive atherosclerotic renal artery stenosis. Issue 10 (22nd April 2022) - Klomjit, Nattawat; Zhu, Xiang-Yang; Eirin, Alfonso; Pawar, Aditya S; Conley, Sabena M; Puranik, Amrutesh S; Ferguson, Christopher M; Kim, Seo Rin; Tang, Hui; Jordan, Kyra L; Saadiq, Ishran M; Lerman, Amir; et al.
ABSTRACT: Background: Renal artery stenosis (RAS) is an important cause of chronic kidney disease and secondary hypertension. In animal models, renal ischemia leads to downregulation of growth factor expression and loss of intrarenal microcirculation. However, little is known about the sequelae of large-vessel occlusive disease on the microcirculation within human kidneys. Method: This study included five patients who underwent nephrectomy due to renovascular occlusion and seven nonstenotic discarded donor kidneys (four deceased donors). Micro-computed tomography was performed to assess microvascular spatial densities and tortuosity, an index of microvascular immaturity. Renal protein expression, gene expression and histology were studied in vitro using immunoblotting, polymerase chain reaction and staining. Results: RAS demonstrated a loss of medium-sized vessels (0.2–0.3 mm) compared with donor kidneys (P = 0.037) and increased microvascular tortuosity. RAS kidneys had greater protein expression of angiopoietin-1, hypoxia-inducible factor-1α and thrombospondin-1 but lower protein expression of vascular endothelial growth factor (VEGF) than donor kidneys. Renal fibrosis, loss of peritubular capillaries (PTCs) and pericyte detachment were greater in RAS, yet they had more newly formed PTCs than donor kidneys. Therefore, our study quantified significant microvascular remodeling in the poststenotic human kidney. RAS induced renal microvascular loss, vascular remodeling and fibrosis. Despite downregulated VEGF, stenotic kidneys upregulated compensatory angiogenic pathways related to angiopoietin-1. Conclusions: These observations underscore the nature of human RAS as a microvascular disease distal to main vessel stenosis and support therapeutic strategies directly targeting the poststenotic kidney microcirculation in patients with RAS. Graphical Abstract: